The oppositional affordances of data activism - Milioni, Dimitra L.; Papa, Venetia (My University, 2022)
This study draws on several data activism projects and applies discursive interface analysis to understand the material means by which activist software strives to empower users vis-à-vis data power. The analysis uncovers four types of oppositional affordances: (i) enabling the use of hidden affordances (ii) imagining new affordances (iii) creating meta-affordances (resignifying perceptible affordances of corporate platforms and reconstructing their meaning), and (iv) creating anti-affordances (hindering or distorting corporate platforms’ affordances to the extent that they do not perform their intended function). Although not without limitations, oppositional affordances reveal the actual agentic possibilities of data activism for users other than activists to affect the very algorithms that produce them as datafied subjects. The proposed typology provides a means for further empirical analysis of critical software and its subversive potential for users. The article concludes with a critical discussion of data activism as a means of vernacular critical praxis.
Keywords: datafication; user agency; Data activism; affordance theory; software analysis